THE EFFECT OF TGT-PUZZLE COOPERATIVE LEARNING TO IMPROVE LEARNING ACHIEVEMENT ON MOLECULAR GEOMETRIC MATERIAL (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2023)
Chemistry can be divided into two concepts: concrete concepts and defined concepts. The geometris of a molecule is one of the defining concepts, because ideas are at the molecular level and are invisible to the naked eye. Therefore, this study was conducted to determine the effect of the TGT Puzzle cooperative learning strategy on the success of learning the material of molecular form. The purpose of this study was to determine whether learning achievement increased after learning the TGT Puzzle cooperative learning strategy in class X IPA MA Hidayatul Ummah Pringgoboyo. This study uses statistical inference technique using paired sample t-test to determine whether learning performance increases after learning with the TGT Puzzle cooperative learning strategy. The method of analysis used paired sample t-test with a significant difference (sig) <0.05. The results of this study indicate an increase in learning achievement after learning with the TGT Puzzle cooperative learning strategy.